An introduction to Middle English - Horobin, Simon (Edinburgh University Press, 2002)
This book is designed to provide undergraduate students of English historical linguistics with a concise description of the language during the period 1100-1500.
Keywords: English language -- Middle English, 1100-1500.; Anglais (Langue) -- 1100-1500 (Moyen anglais); FOREIGN LANGUAGE STUDY -- Old & Middle English.; English language -- Middle English; Middelengels.; 1100 - 1500; Electronic book.